The use of Web 2.0 tools by students in learning and leisure contexts: a study in a Portuguese institution of higher education - Costa, Carolina
This study analyses and compares the use of Web 2.0 tools by students in both learning and leisure contexts. Data were collected based on a questionnaire applied to 234 students from the University of Aveiro (Portugal) and the results were analysed by using descriptive analysis, paired samples t-tests, cluster analyses and Kruskal–Wallis tests. The results show that the tools most used by students in a learning context are video sharing, social network sites and wikis, and that in a leisure context students use social network sites and video sharing more. The profiles of the groups resulting from the cluster analyses reveal that 42% of the students do not use Web 2.0 tools intensively in either one of the contexts. However, findings from comparing the clusters of both contexts show that students who more frequently use the tools in the leisure context are occasional users in the learning context and vice versa. This study contributes to a better knowledge of the student profiles concerning the use of Web 2.0 tools in learning and leisure contexts which can help teachers direct their strategies to the use of the most appropriate tools, thus improving the success of the teaching/learning process.